Training on making flipbook-based digital module for junior high school Javanese language teachers in Purworejo District - Aris Aryanto; Yuli Widiyono; Murhadi Murhadi (Universitas Muhammadiyah Magelang, 2023)
The technological prowess of most junior high school Javanese teachers in Purworejo District is still lacking, especially in the development of innovative digital modules. The purpose of this community service is to provide additional knowledge and skills in developing innovative teaching materials in the form of flipbook-based digital modules for Middle School Javanese teachers in Purworejo Regency. The training implementation method consists of four stages, namely planning, implementation, monitoring and evaluation. All activities ran smoothly and the teachers enthusiastically participated in the training series. The result of this program is an increase in knowledge, motivation and enthusiasm in making flipbook-based learning modules.